Linking Heterogeneous Climate Policies (Consistent with the Paris Agreement) - Michael A. Mehling; Gilbert E. Metcalf; Robert N. Stavins (Fondazione Eni Enrico Mattei (FEEM), 2017)
The Paris Agreement has achieved one of two key necessary conditions for ultimate success – a broad base of participation among the countries of the world. But another key necessary condition has yet to be achieved – adequate collective ambition of the individual nationally determined contributions. How can the climate negotiators provide a structure that will include incentives to increase ambition over time? An important part of the answer can be international linkage of regional, national, and subnational policies, that is, formal recognition of emission reductions undertaken in another jurisdiction for the purpose of meeting a Party's own mitigation objectives. A central challenge is how to facilitate such linkage in the context of the very great heterogeneity that characterizes climate policies along five dimensions – type of policy instrument; level of government jurisdiction; status of that jurisdiction under the Paris Agreement; nature of the policy instrument's target; and the nature along several dimensions of each Party's Nationally Determined Contribution. We consider such heterogeneity among policies, and identify which linkages of various combinations of characteristics are feasible; of these, which are most promising; and what accounting mechanisms would make the operation of respective linkages consistent with the Paris Agreement.
Keywords: Q5; Q56; 330; Climate Policy; Paris Agreement; Nationally Determined Contributions